Book Review: How to Survive the Western Democratising Pressure? - Raun, Alo (Studies of Transition States and Societies, 2013)
Competitive Authoritarianism: Hybrid Regimes After the Cold War by Steven Levitsky and Lucan A. Way, 2010, New York, NY: Cambridge University Press.